A randomized, placebo-controlled trial of ondansetron, metoclopramide, and promethazine in adults - Barrett, Tyler W.; DiPersio, David M.; Jenkins, Cathy A.; Jack, Meg; McCoin, Nicole Streiff; Storrow, Alan B.; Singleton, Lori M.; Lee, Patricia; Zhou, Chuan; Slovis, Corey M. (The American journal of emergency medicine, 2011)
The objective of the study was to assess whether ondansetron has superior nausea reduction compared with metoclopramide, promethazine, or saline placebo in emergency department (ED) adults. This randomized, placebo-controlled, double-blinded superiority trial was intended to enroll a convenience sample of 600 patients. Nausea was evaluated on a 100-mm visual analog scale (VAS) at baseline and 30 minutes after treatment. Patients with a minimum preenrollment VAS of 40 mm were randomized to intravenous ondansetron 4 mg, metoclopramide 10 mg, promethazine 12.5 mg, or saline placebo. A 12-mm VAS improvement in nausea severity was deemed clinically important. We measured potential drug adverse effects at baseline and 30 minutes. Patients received approximately 500 mL of saline hydration during the initial 30 minutes. Of 180 subjects who consented, 163 completed the study. The median age was 32 years (interquartile range, 23-47), and 68% were female. The median 30-minute VAS reductions (95% confidence intervals) and saline volume given for ondansetron, metoclopramide, promethazine, and saline were −22 (−32 to −15), −30 (−38 to −25.5), −29 (−40 to −21), and −16 (−25 to −3), and 500, 500, 500, and 450, respectively. The median 30-minute VAS differences (95% confidence intervals) between ondansetron and metoclopramide, promethazine, and saline were −8 (−18.5 to 3), −7 (−21 to −5.5), and 6 (−7 to 20), respectively. We compared the antiemetic efficacy across all treatments with the Kruskal-Wallis test ( P = .16). Our study shows no evidence that ondansetron is superior to metoclopramide and promethazine in reducing nausea in ED adults. Early study termination may have limited detection of ondansetron's superior nausea reduction over saline.